Southern-hemisphere PMSE: Where are they? - Balsley, B. B. (1993)
We are happy to acknowledge the support of Commandante Hector Soldi (Expedition Leader) and Teniente Italo Huertas (Base Commander) in insuring the installation and ongoing support of Peru's Machu Picchu Base. Additional support from both Peru's Comision Nacional de Asuntos Antartidos (CONAAN) and Consejo Nacional de Ciencias y Technologia (CONCYTEC), the Argentinean Navy, and the Uraguayan Air Force are greatly appreciated. The untiring assistance of S. Villegas and J. Fernandez, who have been associated with this project since its inception, is also gratefully acknowledged. This research is based upon work supported by NSF's Office of Polar Programs under Grant #DPP 922446.